TPACK Implementation in Economic Learning Innovation at SMA Negeri 2 Salatiga - Kristina Dwi Apri Astutik; Bambang Ismanto; Destri Sambara Sitorus (Tarbawi, 2021)
This study aims to determine the application of TPACK in innovations made by teachers in economic learning. The method used in this research is descriptive with a qualitative approach. The subjects in this study were economics teachers and students. Data collection techniques carried out in this study used the methods of observation, interviews, and documentation. The results of this study state that schools have implemented TPACK in economic learning by making innovations to develop students' understanding of economics learning. All teachers already understand technology, so teachers use technology, especially in economics learning. In the economics learning process, teachers use various strategies, models, and learning methods that have been compiled in the lesson plans and innovate through approach, models, and learning methods. In addition to integrating technology and pedagogy, teachers innovate in material knowledge. Along with the development of the curriculum, economics teachers develop themselves to better master the economics material and, thought training could add insight to teachers in mastering the material. TPACK is a new research topic in the world of education in Indonesia. Therefore, the Education Office and related agencies are expected to provide and explain throughout socialization and conduct training on TPACK to add references in the world of education.